Development and Validation of the Online Histrionic Personality Scale (OHPS) Using the DSM-5 Criteria for Histrionic Personality Disorder - Savci, Mustafa; Griffiths, Mark D.; Aysan, Ferda (Springer, 2020)
The present study evaluated personality presentation in online environments in terms of histrionic personality. The aim of the study was to develop the Online Histrionic Personality Scale (OHPS). The OHPS was developed using the diagnostic criteria for histrionic personality disorder (HPD) in the DSM-5 and assesses histrionic behavior in online environments. The present study comprised 381 university students (219 females and 162 males) from four different samples. The validity of the OHPS was investigated utilizing exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and criterion validity. As a result of the EFA, a single-factor structure with an eigenvalue of 3.850 was found and accounted for 48.12% of the total variance. This one-dimensional structure was tested with CFA in two different samples. CFA results show that OHPS had an acceptable fit. The criterion validity of the OHPS was examined with the Desire for Being Liked Scale (DBLS) and the Histrionic Personality Belief subscale of the Personality Belief Questionnaire-Short Form (PBQ-STF). Analysis showed that the OHPS was significantly associated with desire for being liked (r =.65, p <.01) and histrionic personality beliefs (r =.70, p <.01). The reliability of the OHPS was evaluated with Cronbach’s ? internal consistency reliability coefficient and corrected item total correlation coefficient in three different samples. The Cronbach ? internal consistency coefficients of the OHPS were.84 (EFA sample),.88 (CFA sample), and.88 (criterion validity sample). Corrected item total correlation coefficients of OHPS ranged from.53 to.62 in the EFA sample,.47 to.78 in the CFA sample, and.52 to.76 in the criterion validity sample. The distribution of data was examined with floor and ceiling effects in three different samples. Finally, the standard error of measurement (SEM) was calculated in three different samples. There were no floor and ceiling effects in the data, and the SEM values were within acceptable limits. When validity and reliability analyses of the OHPS are considered as a whole, it is concluded that the OHPS is a valid and reliable scale that assesses online histrionic personality among university students. © 2020, Springer Nature Switzerland AG.
Keywords: Histrionic personality; Histrionic personality disorder; Online histrionic behavior; Online histrionic personality